Governance and domestic policymaking in saudi arabia: transforming society (Bloomsbury, 2022)
"Saudi Vision 2030 and the National Transformation Plan 2020 are governmental initiatives to diversify Saudi Arabia's economy and implement nationwide social changes. Media and scholarly attention often describe the success or failure of these ambitious visions. This book shifts the focus to instead examine and evaluate the actual processes of domestic policymaking and governance that are being mapped out to achieve them. The book is unique in its breadth, with case studies from across different sectors including labour markets, defence, health, youth, energy and the environment. Each analyses the challenges that the country's leading institutions face in making, shaping and implementing the tailored policies that are being designed to change the country's future. In doing so, they reveal the factors that either currently facilitate or constrain effective and viable domestic policymaking and governance in the Kingdom. The study offers new and ground-breaking research based on the first-hand experiences of academics, researchers, policy-makers and practitioners who have privileged access to Saudi Arabia. At a time when analysis and reportage on Saudi Arabia usually highlights the 'high politics' of foreign policy, this book sheds light on the 'low politics' to show the extent to which Saudi policy, society, economics and culture is changing"--